Website Performance Testing Using Speed Testing Model: A Case of Reputable Indonesian Journals - Muriyatmoko, Dihin; Aziz Musthafa (Teknik: Jurnal Ilmu Teknik dan Informatika, 2022)
The speed of a web journal to load pages reflects the website performance. It has influenced user satisfaction. This study aims to study and analyze the performance of journal websites in Indonesia that are accredited by SINTA 1 by the Ministry of Research and Technology of the Republic of Indonesia. This test uses parameters owned by GTmetrix tools and calculated using descriptive statistical methods. This research hypothesis regarding the reliability of website speed testing has been tested and confirmed based on experiments. The research involved 61 journal websites, which were taken from December 2019 to February 2020. 366 individual website speed tests from 6 test server region have done, and recommendations have been given on test results. The test result showed that parameter based on PageSpeed score provided the value of 7.9% (grades A to B) and 92.1% (grade C to F) and YSlow score provided a value of 2.5% (grade B) and 97.5% (C to F). The experimental results prove that the performance of the journal website is still a lot in the low category. With the recommendation, it was expected that the speed and responsiveness of the journal website would increase